Engaging Love, Divinity, and Philosophy: Pragmatism, Personification, and Autoethnographic Motifs in the Humanist Poetics of Brunetto Latini, Dante Alighieri, and Giovanni Boccaccio - Prus, Robert (Qualitative Sociology Review, 2014)
Although the works of three early Italian Renaissance poets, Brunetto Latini (1220-1294), Dante Alighieri (1265-1321), and Giovanni Boccaccio (1313-1375), may seem far removed from the social science ventures of the 21st century, these three Italian authors provide some exceptionally valuable materials for scholars interested in the study of human knowing and acting. As central participants in the 13th-14th century “humanist movement” (in which classical Greek and Latin scholarship were given priority in matters of intellectual development), Brunetto Latini, Dante Alighieri, and Giovanni Boccaccio helped sustain an analytic focus on human lived experience. Most of the materials addressed here are extensively fictionalized, but our interests are in the sociological insights that these authors achieve, both in their accounts of the characters and interchanges portrayed in their texts and in their modes of presentation as authors. Although lacking the more comprehensive aspects of Chicago-style symbolic interactionist (Mead 1934; Blumer 1969) theory and research, these early Renaissance texts are remarkably self-reflective in composition. Thus, these statements provide us with valuable insights into the life-worlds of (a) those of whom the authors speak, (b) those to whom the authors address their works, and (c) the authors themselves as people involved in generating aspects of popular culture through their poetic endeavors. More specifically, these writers enable us to appreciate aspects of pragmatist emphases on human knowing and acting through their attentiveness to people’s perspectives, speech, deliberation, action, and interaction. In addressing affective relationships, introducing generic standpoints, and considering morality as community matters, these materials offer contemporary scholars in the social sciences some particularly instructive transhistorical and transcultural comparative and conceptual reference points. Inspired by the remarkable contributions of the three 13th-14th century Italian poets and some 12th- 13th century French predecessors, the Epilogue direct specific attention to the ways in which authors might engage poetic productions as “producers” and “analysts” of fictionalized entertainment.